Towards a learning organisation - Boonen, A. (Educational Sciences, 2000)
As we face a revolutionary move towards e-learning and away from traditional face-to-face training, today's human resource manager implementing technology-supported training needs a concise, practical handbook outlining the choices that have to be made and the implications of each approach. 'Towards a learning organisation' brings human resource managers up-to-date with the various applications that are open to them, such as Electronic Learning Environments, Web based training, Videoconferencing, etc. This handbook provides user-friendly information about emerging technologies for training, checklists and other decision-making tools. Based on broad experience and peppered throughout with case studies and examples from leading European companies and institutions, it also offers plenty of background information including an onverview of network options as well as a handy glossary and further resources list.